Elevated Baseline Salivary Protease Activity May Predict the Steadiness of Gingival Inflammation During Periodontal Healing: A 12-Week Follow-Up Study on Adults - Ulvi Kahraman Gürsoy; Dareen Fteita; Floris J. Bikker; Maria Anastasia Grande; Kamran Nazmi; Mervi Gürsoy; Eija Könönen; Daniel Belstrøm (Pathogens, 2020)
Aim was to profile salivary total protease, Porphyromonas gingivalis gingipain, and neutrophil elastase activities in relation to the resolution of periodontal inflammation, salivary macrophage-derived chemokine (MDC), and macrophage inflammatory protein-1α concentrations. Nonsurgical periodontal treatment was performed in 24 periodontitis patients in a prospective interventional study design. Periodontal clinical parameters were recorded, and stimulated saliva samples were collected at baseline and 2, 6, and 12 weeks after treatment. Salivary total protease and gingipain activities were determined using fluorogenic substrates, elastase activity by chromogenic substrates, and cytokine concentrations by Luminex immunoassay. For statistical analyses, generalized linear mixed models for repeated measures were used. Salivary total protease activity elevated, while gingival inflammation and plaque accumulation decreased 2 and 6 weeks after periodontal therapy. Salivary MDC concentration was elevated 12 weeks after periodontal treatment. Patients with elevated protease activities at baseline in comparison to patients with low baseline total protease activities, had higher levels of gingival inflammation before and after periodontal treatment. In conclusion, elevations in salivary total protease activity seem to be part of periodontal healing at its early phases. Higher levels of salivary total protease activities before periodontal treatment may predict the severity and steadiness of unresolved gingival inflammation.